2022
DOI: 10.2147/jpr.s353249
|View full text |Cite
|
Sign up to set email alerts
|

Pain Assessment in Chinese Parkinson’s Disease Patients Using King’s Parkinson’s Disease Pain Scale

Abstract: Purpose To assess Parkinson’s disease (PD)-related pain using the Chinese translation of King’s Parkinson’s disease Pain Scale (KPPS). Patients and Methods A cohort of 200 patients with primary PD was recruited for this study. Their demographic and clinical features, including age, disease duration, levodopa equivalent daily dose (LEDD), and scores on the Unified Parkinson’s Disease Rating Scale-III (UPDRS III), Hoehn-Yahr Scale (H&Y), Mini-Mental State Examination (MMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 34 publications
2
9
2
Order By: Relevance
“…pain experienced in the last month) of participants in the current study experiencing 1 or more types of pain was 57%. Data from India (using the KPPS – Indian version) and China (using the KPPS – Chinese version) suggest lower prevalence rates, at 52% and 44.5%, respectively, than found in the current study ( 22 , 24 ). However, the period-prevalence in the current study was lower than in other regional studies: 79.6% in Bulgarian patients and 88.6% in Mexico City patients ( 23 , 26 ).…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…pain experienced in the last month) of participants in the current study experiencing 1 or more types of pain was 57%. Data from India (using the KPPS – Indian version) and China (using the KPPS – Chinese version) suggest lower prevalence rates, at 52% and 44.5%, respectively, than found in the current study ( 22 , 24 ). However, the period-prevalence in the current study was lower than in other regional studies: 79.6% in Bulgarian patients and 88.6% in Mexico City patients ( 23 , 26 ).…”
Section: Discussioncontrasting
confidence: 86%
“…Pain intensity, according to the KPPS – Swedish version, was a mean (standard deviation; SD) of 7.84 (12.8) out of a possible 168, which is lower than reported for the KPPS – Chinese version ( 24 ) with a mean (SD) score of 41.2 (26.8), KPPS – Bulgarian version ( 26 ) with a mean score of 21.1 (17.3), and the KPPS – Indian version ( 22 ) with a mean score of 16.02 (10.57). The period-prevalence (i.e.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…[10] Using KPPS, several studies have described the prevalence, severity, and frequency of pain in PD alongside its correlates, but did not represent different populations. Moreover, these studies showed variable frequency and determinants of pain in different countries and ethnicities [11] [5, [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%